HUBUNGAN STATUS GIZI DAN SUSPEK KASUS BARU TB PARU PADA KELUARGA PASIEN TUBERKULOSIS DI WILAYAH KERJA PUSKESMAS TEMBOKREJO KABUPATEN BANYUWANGI TAHUN 2022 - Dita Amanda Deviani; Titis Sriyanti; Masroni Masroni; Yulinar Mashuri (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2022)
Nutritional status is a measure of success in fulfilling nutrition as indicated by weight and height. Nutritional status in this study is the condition of respondent’s health status by measuring weight (kg) divided by height (m²) or Body Mass Index (BMI). Measurement of nutritional status can be used to screen new suspected cases of pulmonary tuberculosis (TB). A person with a thin nutritional status is at risk of developing TB disease compared to the normal one. The purpose of this study was to determine the correlation between nutritional status and new cases suspect of pulmonary TB in the tuberculosis patient’s family in the working area of Tembokrejo Public Health Center, Banyuwangi in 2022. This study used a correlation analytic design with a cross sectional approach and the sampling technique used accidental sampling with 41 respondents as sample. The instrument used for data collection was an observation sheet. Data were analyzed using SPSS with the Fisher’s Excat Test. The results showed that the nutritional status variable obtained a high proportion of pulmonary TB incidence in repondents with underweight nutritional status as many as 2 respondents (4.9%) compared to respondents with normal nutritional status as many as 1 respondent (2.4%). After statistical analysis, the p-value was 0.155, which means Ho was accepted and Ha was rejected, so it can be conluded thet there was no correlation between nutritional status and new cases suspect of pulmonary TB in the tuberculosis patients’ family in the working area of Tembokrejo Public Health Center Banyuwangi in 2022. A person with poor nutritional status makes the diseases attack their body easier, besides it causes the immune system decrease, so it is necessary to improve nutritional status to avoid transmission of disease including tuberculosis.